Hybrid quantum sensing in diamond - Wang, Ning; Cai, Jianming (Frontiers in Physics, 2024)
Quantum sensing is a quantum technology for ultrasensitive detection, which is particularly useful for sensing weak signals at the nanoscale. Nitrogen vacancy centers in diamond, thanks to their superb quantum coherence under ambient conditions and the stability of the material in extreme and complicated environments, have been demonstrated as promising quantum probes in multi-parameter sensing. Their spin properties make them particularly sensitive to magnetic fields, but they are insensitive to temperature, electric field, pressure, etc., and even immune to some bio-parameters (e.g., pH and glucose concentration). Recently, hybrid quantum sensing has emerged as a promising avenue for further enhancing the capabilities of diamond sensors. Different techniques can potentially improve the sensitivity, range of detectable parameters, and sensing frequencies of diamond sensors. This review provides an overview of hybrid quantum sensing using diamond. We first give a brief introduction to quantum sensing using diamond, and then review various hybrid sensing schemes that have been developed to enhance the sensing capabilities of diamond sensors. Finally, the potential applications and challenges associated with hybrid quantum sensing in diamond are discussed.